Uso de experimentos virtuais no ensino de física - Santos, Raphael de Souza [UNESP]; Lopes, Rosemara Perpetua; Feitosa, Eloi da Silva [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
The aim of this study is to contribute to the integration of new technologies to the teaching practice of the Basic Education teacher. One of its specific objectives is to develop and make available on the Internet and CD-room teaching materials to facilitate the use of software by the teacher at school. Scripts were produced for the use of virtual experiments (applets) in Physics by the teacher, from a selection of simulations, freely available on the Internet, which can be used offline.

O objetivo geral deste trabalho é contribuir para a integração das novas tecnologias à prática pedagógica do professor da Educação Básica. Um de seus objetivos específicos consiste em elaborar e disponibilizar na Internet e CD-room material didático que facilite o uso de software pelo professor na escola. Produziram-se roteiros para o uso de experimentos virtuais (applets) de Física pelo professor, a partir de uma seleção de simulações, disponíveis gratuitamente na Internet, e que podem ser utilizados offline.
Keywords: New technologies; Educational software; Physics virtual laboratory; Teaching materials; Novas tecnologias; Software educacional; Laboratório virtual de física; Material pedagógico